Accountability Determination Analysis on Islamic Boarding Schools in Bireuen Regency - Naz’aina Naz’aina; Hendra Raza; Murhaban Murhaban (Budapest International Research and Critics University, 2022)
This study aims to: examine the effect of charismatic leadership, human resource competence, the use of Technology in increasing the accountability of Islamic boarding schools. The method used in this research is descriptive and verification methods. The population in this study were all 164 Islamic boarding schools in Bireuen Regency. The population characteristics (sampling frame) were active Islamic boarding schools with several students above 500. Islamic boarding schools that met the population characteristics were 33. The census determined the sample. The instrument used in data collection is a questionnaire. Questionnaires were given to Islamic boarding school leaders, teachers, and heads of accounting/administration/finance sections. The total number of respondents was 99. The collected data were analyzed using a PLS approach using a structural equation model (SEM). The results showed that charismatic leadership and HR competence positively and significantly affected accountability. While the use of Technology has no significant positive impact on accountability.